Internal Audit and its Role in Detecting Accounting Errors - Shaymaa Qasim Thamer (American Journal of Economics and Business Management, 2022)
The research aimed through the internal audit in discovering errors, as the research was built on the following hypotheses: 1) There is a correlation with a significant relationship between internal audits and accounting errors. 2) There is a significant effect between internal audits and accounting errors. The researcher prepared the practical side by using the questionnaire method, a sample questionnaire from the research sample. The questionnaire included two axes, distributed to them, and a form, and twenty were presented, and the number of times of extraction, and the number of forms and those subject to analysis (50) forms. During which the most important conclusions were reached: 1- Regarding the audit variable (the independent variable in the model) and its role in discovering accounting errors (the dependent variable in the model), despite its importance, he was able to explain (meaning the clarification coefficient R2) with a percentage of (35%) of the explanations and the rest of the percentage (65%)) due to other factors not shown in the model. 2- Most of the contributors in the research sample agreed on the importance of both skill and interest in internal auditing in discovering accounting errors. The percentage of agreement (92%) of the sample drawn was most of their accounting specialties. During which the recommendations were reached, the most important of which are: - 1- The necessity of paying attention to the scientific and professional qualification of the internal auditor, developing their performance, and using modern technologies to accomplish tasks through the development of continuous training programs for employees to improve performance in line with new developments. 2- The need to involve accountants in dedicated courses to develop the efficiency and effectiveness of employees working in the accounts department for accounting principles, assumptions, and standards, which helps reduce accounting errors.